(untitled) (Journal of Economic Research & Business Administration, 2016)
Public service reforms in 2013 have shown that Kazakhstan needs fur-ther improvements in the mechanism of selection of civil servants as well as the construction of the system of their career advancement. The construction of professional autonomous state apparatus in the country is not finished yet. Changes has to be done in human resource polices and in the image and ethics of public servants. The solution of this kind of problems is solved by creating high quality system of selecting public servants and building of an effective system of planning their career. Therefore, a new bill has been drafted in Kazakhstan in order to create new framework of selecting public servants. This article tells about the features of these innovations and their impact on the quality of public service. Authors suggest to include a work experience in relevant public ser-vice sector into the requirements list of vacant positions.